Nursing ethics - Jahn Kassim, Puteri Nemie (2012)
In fulfilling their responsibilities, nurses are often challenged with clinical situations that have ethical conflicts. These unresolved conflicts may cause feelings of frustration and powerlessness, which can lead to compromises in patient care, job dissatisfaction, disagreements among those in the healthcare team. Nurses need skills and guidance to help resolve ethical conflicts. In any event, nurses are encouraged to raise awareness and actively discuss the ethical issues in their practice settings to decrease feelings of uncertainty and find the best solutions to resolve these ethical conflicts.